2021
DOI: 10.1007/s10665-020-10082-3
|View full text |Cite
|
Sign up to set email alerts
|

The method of fundamental solutions for Brinkman flows. Part I. Exterior domains

Abstract: This is a repository copy of The method of fundamental solutions for Brinkman flows. Part I. Exterior domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…For the Brinkman flow we took the parameters µ = 1 and κ = 1. Numerical experiments carried out in Part I [17] in the case of exterior Brinkman flows revealed that there is no significant change in accuracy of the numerical results when the parameters R, µ and κ are varied. For the arbitrary star-shaped obstacle (3.5) the additional traction (stress force) data (2.4) is numerically simulated by first solving the direct problem (1.1)-(2.3) with known D using the MFS (with different numbers of degrees of freedom M and N than those employed in the inverse problem to avoid committing an inverse crime).…”
Section: Numerical Examplesmentioning
confidence: 96%
See 2 more Smart Citations
“…For the Brinkman flow we took the parameters µ = 1 and κ = 1. Numerical experiments carried out in Part I [17] in the case of exterior Brinkman flows revealed that there is no significant change in accuracy of the numerical results when the parameters R, µ and κ are varied. For the arbitrary star-shaped obstacle (3.5) the additional traction (stress force) data (2.4) is numerically simulated by first solving the direct problem (1.1)-(2.3) with known D using the MFS (with different numbers of degrees of freedom M and N than those employed in the inverse problem to avoid committing an inverse crime).…”
Section: Numerical Examplesmentioning
confidence: 96%
“…Another possibility for the inhomogeneous condition (2.3) is to represent an internal fluid velocity measurement in the exterior domain R 2 \D, as previously considered in Part I [17].…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…For solving the inverse problem (1)-( 5) and (11) to detect the obstacle (12), we minimize the least-squares functional…”
Section: Inverse Geometric Problemmentioning
confidence: 99%
“…In such a situation, inverse modeling offers a valuable approach to overcome these challenges by utilizing observed effects or indirect measurements to infer the properties, shapes, sizes and locations of submerged obstacles. There are several papers about the identification of obstacles immersed in some different types of fluids such as, potential [5], Stokes [18,3,2], Oseen [15,11], Brinkman [12,13] or Navier-Stokes [1,7]. The studies in [1,7] were mainly theoretical and they dealt with the simpler Dirichlet boundary conditions for which the existence and uniqueness of solution theory is available [23].…”
Section: Introductionmentioning
confidence: 99%